Pengaruh Kompetensi Sumber Daya Manusia dan Pemanfaatan Teknologi Informasi Terhadap Kualitas Laporan Keuangan Dinas Pendidikan dan Kebudayaan Kabupaten Padang Lawas - Kurnia Harahap; Tanjung, Ali Mukti; Prayoga, Bobby Indra (eScience Humanity Journal, 2024)
The 2020 Padang Lawas Regency Education and Culture Service Financial Report was prepared to provide relevant information regarding the financial position and all transactions carried out by the reporting entity during 1 (one) reporting period. Financial reports are mainly used to compare the realization of income, expenditure, transfers and financing with the established budget, assess the condition of the financial balance, assess the effectiveness and efficiency of a reporting entity and help determine its compliance with statutory regulations. This research is a correlational descriptive research. The research samples in this study were employees of the Padang Lawas Regency Education and Culture Service, totaling 30 employees out of 31 employees. Research instrument by distributing questionnaires. Data collection techniques using literature study, documentation, questionnaires and interviews. Validity and Reliability Test. The classic assumptions in this research consist of normality of multicollinearity and heteroscedasticity test data. Data Analysis Techniques using Multiple Linear Regression analysis. The research results show that there is a significant influence on the use of information technology from the Padang Lawas Regency Education and Culture Service of 0.767 or 76.7% in the strong category. This means that the better the use of information technology, the higher the quality of the financial reports. This can be seen from the assessment of each indicator, namely speed, consistency, precision and reliability.